RESPONSE OF 2 VARIETY OF Solanum melongena L. ON THE GRANTING OF COW’SBIO URINE - Ahmad Muhamad Muatho (JARES (Journal of Academic Research and Sciences), 2017)
Treatment A: combination of green eggplant varieties with urine dose 80 cc 2. Treatment B: combination of green eggplant variety with urine dose 120 cc 3. Treatment C: combination of eggplant varieties green with a urine dose of 160 cc 4. Treatment D: combination of green eggplant varieties with urine dose 200 cc 5. Treatment E: combination of violet eggplant varieties with urine dose 80 cc 6. Treatment F: combination of violet eggplant varieties with urine dose 120 cc 7. Treatment G: combination of violet eggplant varieties with urine dose 160 cc 8. Treatment H: combination of violet eggplant varieties with urine dose 200 cc, treatment repeated 3 times so obtained 24 unit experiment, each experiment plot consist of 15 plants. Parameters observed include plant height, number of leaves, total fruit weight, fruit length and total amount of fruit per plant. Giving of cow urine has a significant effect on the parameters of plant height, number of leaves, fruit weight, fruit length, number of fruit per plant. The best treatment is a combination of violet eggplant and 160cc bio urine / plant which is no different from 200 cc / plant. Keywords: Eggplant, Bio Urine Â Received: 2 February, 2017; Accepter: 15 March, 2017